Dynasty Politics in Succession of Village Leadership: A Case Study in the Village of Cileunyi Wetan, Indonesia - Hadi Prabowo; Sri Hartati (GoAcademica Research & Publishing, 2019)
The purpose of this research is to find out the factors causing dynastic politics and the impact of dynastic politics on village leadership for community development in Cileunyi Wetan Village, Cileunyi District, Bandung Regency. This study uses qualitative methods with data collection techniques such as interviews, observation, and study documentation. Dynasty politics is a process of regenerating power for the interests of the political elite that aims to maintain power by placing their families or relatives in certain positions in the field of government. The practice of dynastic politics in the village of Cileunyi Wetan was an attempt to maintain power by the village head's family for several periods. The relationship between the village head and the former village head was uncle and father, who still had influence in the community. The dynasty in the village leadership in the village of Cileunyi Wetan was caused by the strength of capital (economy), the strength of family networks, and the existence of unhealthy democratic practices. The dynastic political impact of village leadership on community development in the village of Cileunyi Wetan is the control of economic resources in the village by a group of people, and the existence of nepotism in the recruitment of village government officials.